Implementation process of quality management tools (2020)
The aim of the article is to describe the research focused on understanding the relationship between quality management tools and results in the training of students of educational establishments of the city of Manizales. To achieve this objective, a process of qualitative nature was developed with a comprehensive intention in mind, based on hermeneutics: a reading of a phenomenon of the reality of management processes to interpret the logical relationship between quality management tools and results in the formation of students in schools and the impact it has had on education. The main findings allowed an approach to the main theoretical contributions focused on the implementation process of quality management tools and training of students in educational establishments. However, we found that nationwide investigations are very few and show a significant co-relation between educational standards and discourse. In recent years, these studies emphasize the development plans of the political and administrative authorities, but even these proposals and speeches are not reflected effectively in the socialcultural transformation that the country needs in relation to processes of the quality management system.